In-Phase and Quadrature Imbalance Modeling, Estimation, and Compensation - Li, Yabo.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This book provides a unified IQ imbalance model and systematically reviews the existing estimation and compensation schemes. It covers the different assumptions and approaches that lead to many models of IQ imbalance. In wireless communication systems, the In-phase and Quadrature (IQ) modulator and demodulator are usually used as transmitter (TX) and receiver (RX), respectively. For Digital-to-Analog Converter (DAC) and Analog-to-Digital Converter (ADC) limited systems, such as multi-giga-hertz bandwidth millimeter-wave systems, using analog modulator and demodulator is still a low power and low cost solution. In these kind of systems, the IQ imbalance cannot be ignored. By explaining a variety of assumptions and models of IQ imbalance, the author provides a helpful resource for those who are new to this complex topic. The intended audience of this book is researchers working on the IQ imbalance as well as the system design engineers who use IQ imbalance in their systems.
Introduction -- The IQ Imbalance Model -- Frequency Independent IQ Imbalance Estimation and Compensation -- Frequency Dependent IQ Imbalance Estimation and Compensation.
Keywords: Engineering; Telecommunication; Engineering; Communications Engineering, Networks; Signal, Image and Speech Processing